Cognitive functioning of women in pregnancy and early postpartum - Płotek, Włodzimierz; Czarnecka-Iwańczuk, Marta; Grześkowiak, Małgorzata (Journal of Medical Science, 2017)
Pregnancy and early postpartum is an extremely stressful time in a woman’s life. Emotional and cognitive functioning are mutually interconnected. The psyche also influences the physical health on the functional and physical basis. The physiological hormonal changes adapt woman to the development and labour of a child and reflect in the central nervous system functioning. In the presented manuscript, the basic psychological problems accompanying women in this period, as well as mutual relationships between the hormonal and central nervous systems during pregnancy and early postpartum have been presented.
Keywords: pregnancy; postpartum; cognitive functioning